Exploitation of Unconventional Oil and Gas Resources Hydraulic Fracturing and Other Recovery and Assessment Techniques - Imo-Imo Eshiet, Kenneth (IntechOpen, 2019)
The stimulation of unconventional hydrocarbon reservoirs is proven to improve their productivity to an extent that has rendered them economically viable. Generally, the stimulation design is a complex process dependent on intertwining factors such as the history of the formation, rock and reservoir fluid type, lithology and structural layout of the formation, cost, time, etc. A holistic grasp of these can be daunting, especially for people without sufficient experience and/or expertise in the exploitation of unconventional hydrocarbon reserves. This book presents the key facets integral to producing unconventional resources, and how the different components, if pieced together, can be used to create an integrated stimulation design. Areas covered are as follows: • stimulation methods, • fracturing fluids, • mixing and behavior of reservoir fluids, • assessment of reservoir performance, • integration of surface drilling data, • estimation of geomechanical properties and hydrocarbon saturation, and • health and safety. Exploitation of Unconventional Oil and Gas Resources: Hydraulic Fracturing and Other Recovery and Assessment Techniques is an excellent introduction to the subject area of unconventional oil and gas reservoirs, but it also complements existing information in the same discipline. It is an essential text for higher education students and professionals in academia, research, and the industry.